The Association Between the Use of the Education Benefits from the G.I. Bill and Veterans' Health. Issue 5 (27th February 2018) - Rumery, Zachary R; Patel, Nilam; Richard, Patrick
Abstract: Background: There is limited knowledge on the impact of education on veterans' health in the United States. This study specifically examines the relationship between the education benefits from the G.I. Bill and veterans' health. Methods: This study used data from the 2010 National Survey of Veterans. The subjects for this study were 5, 052 veterans who were eligible to receive G.I. Bill benefits, representing a total of about 12.7 million non-institutionalized veterans in the United States in 2010. The dependent variables included self-reported health status and smoking behavior. The key independent variable was whether veterans used the education benefits from the G.I. Bill compared with those who were eligible but did not use them. Findings: Results from multivariate regression analyses showed that those who used the education benefits from the G.I. Bill were 4% less likely to report fair/poor health ( p < 0.01) and 3% less likely to report any smoking ( p < 0.05) compared with those who did not use the education benefits. Additional analyses showed that using the education benefits to attend college decreased the probability of being in fair/poor health by 4% ( p < 0.10) and being a smoker by 4% ( p < 0.05) compared with those who did not attend college but used their benefits for non-college attainment such as business, technical, or vocational schools. More importantly, a larger association was found between the use of the education benefits from the G.I. Bill to obtain a college degree and fair/poor health (7%, p < 0.05) and smoking behavior (9%, p < 0.01) compared with those who attended college but did not obtain a college degree. Discussion: This study shows that providing opportunities for service members to complete their education also has important health benefits.